Prevention of Iodinated Contrast Media-Induced Hyperthyroidism in Patients with Euthyroid Goiter - Pelewicz, Katarzyna (Eur Thyroid J, 2021)
INTRODUCTION: Iodinated contrast media (ICM)-induced hyperthyroidism is an underestimated, potentially severe condition; however, its prevention has not been sufficiently investigated. The aim of this study was to evaluate the influence of ICM on thyroid status, the advantages of prophylactic therapy for iodine-induced hyperthyroidism (IIH) in patients with euthyroid goiter and cardiovascular comorbidities, and the association between the incidence of IIH and thyroid volume. METHODS: Thirty-six euthyroid patients undergoing procedures involving ICM administration were divided into 2 groups: the first group (n = 13) received prophylactic treatment with thiamazole or thiamazole combined with sodium perchlorate during ICM exposure; the second group (n = 23) did not receive prophylaxis. Thyroid-stimulating hormone levels were evaluated before and after ICM, and thyroid hormone levels were assessed after ICM at different points in time. The morphology of the thyroid was evaluated by ultrasonography. RESULTS: Twenty-one patients (58%) developed hyperthyroidism after ICM. Hyperthyroidism was observed more frequently in the group without prophylactic treatment than in the group with prophylaxis (65 vs. 15%, respectively; p = 0.006). No cases of overt hyperthyroidism were observed in the group receiving thiamazole with sodium perchlorate. IIH persisted for a median time of 52.5 days. Larger thyroid volume was associated with a significantly higher occurrence of ICM-induced hyperthyroidism (p = 0.04). CONCLUSIONS: Patients with euthyroid goiter receiving ICM are at risk of developing hyperthyroidism. The occurrence of hyperthyroidism after ICM in euthyroid patients with goiter is higher in those with larger thyroid volume. The frequency of ICM-induced hyperthyroidism in euthyroid patients with goiter is lower in those receiving prophylactic therapy with thiamazole in monotherapy or in combination with sodium perchlorate than in those not receiving prophylactic treatment.